Local Government Policy on Regulating Land Use Conversion: Demolition of Hibisc Fantasy - Qurrota Aini Rahma Ramadhani; M Ilham Hidayatul Kahfi (Catalist Indo Publisher, 2026)
Background This research examines local government policies in dealing with the demolition of the Hibisc Fantasy tourism area built on tea plantation land without permission for a change of use. The conversion of this land has caused environmental damage, including a reduction in water catchment areas that trigger flash floods from Puncak to Jakarta and Bekasi. Methods Using a descriptive qualitative approach through literature study, this research analyzes the legal basis, chronology of violations, and social dynamics resulting from this policy. Results Based on Government Regulation Number 16 of 2021 and 2004, the demolition was carried out to enforce the law and restore ecological functions. However, this policy sparked protests due to socio-economic impacts such as job losses and disruptions to the micro economy. The government responded with greening programs and compensation. Conclusions The results of the study indicate the need for a more holistic approach so that law enforcement does not neglect the social and economic dimensions of the community.